Menjaga Tradisi, Membangun Prestasi: Semarak Turnamen Bola Kaki dan Takraw di Jorong Atas Laban Wujudkan Persatuan Pemuda Nagari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Traditional sports tournaments such as football and sepak takraw are not merely competitive events, but also serve as vital means to preserve cultural heritage and strengthen the social bonds within the community. This article explores the festive and community-rich organization of football and takraw tournaments held in Jorong Atas Laban, Nagari Halaban. The event aims to foster sportsmanship, enhance youth solidarity, and reinforce local identity through the preservation of traditional sports practices. In addition to providing entertainment for the community, the tournament also serves as a momentum for youth development towards greater achievement.The participatory nature of the event, the enthusiastic involvement of the community, and the positive outcomes observed indicate that such activities can be strategic tools for social and cultural development at the local level. Using a qualitative approach, data were collected through direct observation, in-depth interviews with community leaders, youth, organizing committees, and documentation of the event.The findings show that the tournament positively impacts youth participation in social activities, strengthens the spirit of cooperation (gotong royong), and revives a sense of togetherness that had started to fade. Local cultural values such as consensus (musyawarah), sportsmanship, and kinship were deeply reflected throughout the event. Beyond being a healthy competition, the tournament symbolizes a grassroots spirit of building progress initiated by the community itself. It has proven to be one of the strategic efforts in realizing community-based social development rooted in local wisdom.